Environmental strategies for the red ceramic industry from the State of Rio Grande do Sul - Grigoletti, Giane de Campos (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
In Brazil, there is a scarcity of studies that have assessed the impacts of the production of building materials. Such studies play a major role in defining requirements for the choice of materials based on their environmental and social impacts. The purpose of this paper is to discuss the main impacts of the production of ceramic brick, tiles and blocks in the state of Rio Grande do Sul, and to suggest strategies that can be adopted by the red ceramic industry for improving its impact in the environment and in the community where the plants are located. Multiple-case studies involving eight small, medium and large sized companies were carried out. The data collected were concerned with the use of raw materials, energy sources, waste production, sources of CO2 emission and working conditions. The study indicated that this sector has carried out a number of successful initiatives that aim to reduce its environmental impact, such as the consumption of waste from other industries as raw materials and the use of renewable energy sources. However, the case studies indicated that further improvements are necessary in the reduction of waste, improvement of working conditions, and organization of the production process.